Comparison Of Nasal Glucocorticoid, Antileukotriene Versus Combination Of Antileukotriene And Antihistamine In Treatment Of Seasonal Allergic Rhinitis - Piracha, Adia Bushra; Chaudhry, Sadia; Alamgir, Ashar; Kousar, Amna; Imtiaz, Nimra; Sahar, Saba (Journal of Rawalpindi Medical College, 2025)
Objective: This study aimed to compare the efficacy of nasal glucocorticoid combined with antileukotriene therapy versus a combination of antileukotriene and antihistamine therapy in managing symptoms of seasonal allergic rhinitis. Methods: A randomised clinical trial was conducted from January 2024 to July 2024, involving 200 patients diagnosed with seasonal allergic rhinitis. Participants were randomly assigned to two groups of 100 each. Group A received a combination of nasal glucocorticoid and antileukotriene, while Group B received a combination of antileukotriene and antihistamine. Patients with significant respiratory comorbidities, ongoing systemic corticosteroid use, or hypersensitivity to the study medications were excluded. Symptom severity was assessed at four-week intervals using a pre-designed proforma, and statistical analysis was conducted to evaluate differences in symptom control between the two groups. Results: Group A demonstrated superior symptom control compared to Group B across all variables. Nasal obstruction was significantly less frequent in Group A (12.0%) compared to Group B (40.0%, p=0.0001). Similarly, rhinorrhea was observed in 46.0% of Group A compared to 69.0% of Group B (p=0.001). Itching and sneezing were also significantly better managed in Group A, with rates of 40.0% and 68.0% compared to 76.0% and 91.0% in Group B, respectively (p=0.0001). These findings highlight the enhanced efficacy of glucocorticoid-antileukotriene therapy in managing seasonal allergic rhinitis. Conclusion: Nasal glucocorticoid combined with antileukotriene therapy provides significantly better symptom relief for seasonal allergic rhinitis compared to the combination of antileukotriene and antihistamine. This regimen effectively addresses inflammatory pathways, ensuring comprehensive symptom control and improved patient outcomes.